2020
DOI: 10.1088/1742-6596/1511/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of elementary school students’ difficulties in mathematical problem-solving

Abstract: One of the goals of learning mathematics is that students can solve mathematical problems in particular that can then solve problems in everyday life. In the process of solving problems, the skills that students must also possess are the ability to understand the problem, the ability to compose mathematical models of a problem and interpret the solution. In practice, however, students will encounter difficulties in resolving unavoidable problems. The purpose of this study is: 1) to explain the difficulties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Finally, it was revealed that most learners had difficulty solving mathematical word problems and communicating their thinking through writing (Peterson, McAuliffe & Vermeulen, 2017). For example, Kusumadewi and Retnawati (2020) outlined areas of difficulty found from their study that: students' problem solving ability was low, thus they encounter difficulty in locating keywords from problems because they lack the ability and hence result into guessing the solution without going through the completion process; they have difficulty in modelling the problem into mathematical form; they have difficulty in making decision on how to resolve problems; and have difficulty in counting operations, so that they interpret conclusions that are not appropriate to the problem.…”
Section: General Pattern Of the Findings Of The Studies On Problem So...mentioning
confidence: 99%
“…Finally, it was revealed that most learners had difficulty solving mathematical word problems and communicating their thinking through writing (Peterson, McAuliffe & Vermeulen, 2017). For example, Kusumadewi and Retnawati (2020) outlined areas of difficulty found from their study that: students' problem solving ability was low, thus they encounter difficulty in locating keywords from problems because they lack the ability and hence result into guessing the solution without going through the completion process; they have difficulty in modelling the problem into mathematical form; they have difficulty in making decision on how to resolve problems; and have difficulty in counting operations, so that they interpret conclusions that are not appropriate to the problem.…”
Section: General Pattern Of the Findings Of The Studies On Problem So...mentioning
confidence: 99%
“…The cultivation of numeracy literacy in schools is crucial, and careful planning is necessary to ensure that it runs smoothly [11]. Students encounter difficulties in resolving mathematical problems, such as difficulty in finding keywords from problems in questions, modeling the problem into mathematical form, and deciding how to resolve the problem [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, primary school students' content knowledge and mathematical prerequisites are often problematic (Achmetli, Schukajlow, & Rakoczy, 2019). So, primary school students have difficulty in solving problems (Kusumadewi & Retnawati, 2020).…”
Section: Introductionmentioning
confidence: 99%